Placenames Used as Nicknames: A Study of Major League Baseball Players - James K. Skipper (Names, 1990)
Abstract From the beginning of major league baseball, at least 122 players have had nicknames taken from placenames, the majority used in the early twentieth century. These nicknames were of several types and came from many places, mostly the American South. Understanding how these nicknames came about increases our understanding of nicknames and extends our knowledge of placenames.